Enhanced lateral resolution in continuous wave stimulated emission depletion microscopy using tightly focused annular radially polarized excitation beam. Issue 9 (28th May 2019) - Lim, Geon; Kim, Wan‐Chin; Oh, Seunghee; Lee, Hyungsuk; Park, No‐Cheol
Abstract: The lateral resolution of continuous wave (CW) stimulated emission depletion (STED) microscopy is enhanced about 12% by applying annular‐shaped amplitude modulation to the radially polarized excitation beam. A focused annularly filtered radially polarized excitation beam provides a more condensed point spread function (PSF), which contributes to enhance effective STED resolution of CW STED microscopy. Theoretical analysis shows that the FWHM of the effective PSF on the detection plane is smaller than for conventional CW STED. Simulation shows the donut‐shaped PSF of the depletion beam and confocal optics suppress undesired PSF sidelobes. Imaging experiments agree with the simulated resolution improvement. Abstract : In this study, point spread function engineering method with annular radially polarized excitation beams in continuous wave stimulated emission depletion is used to improve lateral resolution. This has the advantage of increasing the depletion beam power required to achieve the same resolution.